The influence of environmental factors on metabolic activity of cancer cells - KOZIOROWSKA, ANNA; STATS, KATARZYNA; ROMEROWICZ-MISIELAK, MARIA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2016)
The paper presents the results of viability of breast cancer cells under the influence of electromagneticfield. MCF-7 cell line was subjected to an electromagnetic field with a frequency of5 Hz, 60 Hz and 120 Hz and an MTT assay was performed immediately after the influence of thefield and after 24 hours. No statistical difference was demonstrated in cell viability immediatelyafter exposure to EMF, and there are demonstrated differences in the case of field frequencies of5 Hz and 120 Hz within 24 hours after exposure.